"Umysł widzący swoje światło" w nauce duchowej Ewagriusza z Pontu - Misiarczyk, Leszek (2016)
Ewagriusz z Pontu w swojej nauce duchowej przedstawia tzw. „modlitwę czystą”, która jest modlitwą nie tylko pozbawioną jakiegokolwiek kontaktu z rzeczami materialnymi, ale również z jakimkolwiek materialnym wyobrażeniem nous. Taki rodzaj głębokiej modlitwy jest jednocześnie źródłem poznania Boga. Umysł (nous), który osiąga stan tak głębokiego oczyszczenia podczas modlitwy doświadcza światła Bożego i widzi siebie jako świecący. Ewagriusz precyzuje, że umysł widzi siebie samego w kolorze szafiru lub nieba a niekiedy jako gwiazdę. Badacze jego pism od lat zastanawiają się czy według niego to światło pochodzi od samego umysłu czy też od Boga. Mnich z Pontu, jak się wydaje, łączy te dwa światła ze sobą uważając je jednak za oddzielone. Światło własne nous jest tylko odbiciem światła Bożego jak księżyc odbija światło słońca. Choć umysł nie jest źródłem swego światła, to jednak jego światło jest realne. W chwilach głębokiego duchowego zjednoczenia z Bogiem Jego światło oświeca ludzki nous i go przemienia w świecący i widzący światło.
The monk Evagrius of Pontus (345-399 AD) presents in his spiritual doctrine the concept of "pure prayer", that is, prayer not only devoid of any contact with material things but also divorced from any concrete image in the nous (i.e., the mind or intellect). This type of deep prayer becomes a source for the knowledge of God. Upon reaching this state of deep purification, the nous experiences during prayer the light of God and also perceives himself as radiant. Evagrius specifies that the nous sees itself in the color of the sapphire or in sky-blue, or even as a star. Scientists for a long time asked themselves whether, for Evagrius, this light originated within the mind itself, or came from God. It seems that monk of Pontus joins these two lights together, although considering them always as separate. The light of nous itself is but a reflection of the divine light, in the same way that the moon reflects the light of the sun. Even if the nous is not the source of its own light, nevertheless its light is real. In a time of deep spiritual union with God, His light illuminates the human nous and turns it into radiance.
The monk Evagrius of Pontus (345-399 AD) presents in his spiritual doctrine the concept of "pure prayer", that is, prayer not only devoid of any contact with material things but also divorced from any concrete image in the nous (i.e., the mind or intellect). This type of deep prayer becomes a source for the knowledge of God. Upon reaching this state of deep purification, the nous experiences during prayer the light of God and also perceives himself as radiant. Evagrius specifies that the nous sees itself in the color of the sapphire or in sky-blue, or even as a star. Scientists for a long time asked themselves whether, for Evagrius, this light originated within the mind itself, or came from God. It seems that monk of Pontus joins these two lights together, although considering them always as separate. The light of nous itself is but a reflection of the divine light, in the same way that the moon reflects the light of the sun. Even if the nous is not the source of its own light, nevertheless its light is real. In a time of deep spiritual union with God, His light illuminates the human nous and turns it into radiance.
Keywords: światło; umysł; Ewagriusz z Pontu; światło